Assessing Knowledge and Preventive Practices Regarding Infectious Diseases Among Healthcare Workers in Hail City, Saudi Arabia - Sandro Costanilla Villareal (Jurnal Keperawatan Indonesia)
Studies suggest that there may be gaps in knowledge and compliance with infection control measures among healthcare workers in Saudi Arabia. This study aimed to determine the knowledge of, and preventive measures employed by the healthcare workers in Hail City, Saudi Arabia, regarding infectious diseases. A cross-sectional design was employed, and the study participants were 265 healthcare workers aged 18 or older who were currently employed at government hospitals, involved in patient care or essential healthcare services, and fluent in English. Healthcare workers on leave, with cognitive impairments, with language barriers, or who refused to participate in the study were excluded. Data collection took place between November and December 2022. Overall, there was a high percentage of correct responses During the surge of the highly infectious disease known as coronavirus disease 2019 (COVID-19), which reached pandemic levels, most of the participants wore gloves while at work and wore masks when leaving the house.. None of the participants went to crowded places (100%). Of note, the participants’ educational attainment (p < .000) and education on COVID-19 (p = .001) were found to have significant relationships with their knowledge. Accordingly, sex (p < .000), educational attainment (p < .000), occupation (p = .001), and education on COVID-19 (p < .000) were found to have significant relationships with employment of COVID-19 preventive measures. The healthcare workers in this study have a good understanding of COVID-19 and are taking appropriate preventive measures to protect themselves and others from it. However, ongoing education and training are crucial to ensure that all healthcare workers possess the necessary knowledge and skills to respond effectively to future health crises.